Bimbingan Teknis Menulis Artikel Ilmiah dan Esai Konten Budaya Lokal Bagi Masyarakat Kota Singkawang - Gunta Wirawan; Zulfahita Zulfahita; Safrihady Safrihady; Wahyuni Oktavia; Eti Sunarsih; Sofia Nur Havizah (BALE LITERASI, 2026)
Scientific articles and essays play a strategic role in documenting and promoting the richness of local traditions. Therefore, writing about local culture is an effort to preserve identity amidst the increasingly strong current of globalization. This Community Service (PKM) activity aims to foster and increase interest in writing scientific articles and essays. The solutions offered are: 1) Providing participants with an understanding of the importance of writing scientific articles and essays with local cultural content. 2) Holding intensive technical guidance on writing scientific articles and essays with local cultural content. This PKM activity is carried out in three main stages, namely: 1) Preparation, namely an initial discussion with the service partner (Singkawang City Library) to identify the need for technical guidance on writing scientific articles and essays. 2) Implementation, to improve the writing skills of participants, the team will hold technical guidance. 3) Evaluation, observations are conducted to observe the participation and involvement of participants in each technical guidance session. In addition, a written test and questionnaire are carried out. The results of the activity showed that the participation and involvement of participants in each technical guidance session, overall, were in the very good category, seen from the participants' skills in writing scientific articles and essays, enthusiasm, level of understanding of participants, and activeness during the technical guidance. A total of 62 participants were in the very good category (78%), 14 participants were in the good category (17%), and 4 participants were in the fairly good category (5%). In addition, the results of the questionnaire responses of 75 participants (93.75%) of 80 participants thought the technical guidance on writing scientific articles and essays on local cultural content was very useful, 2 participants thought it was less useful, and 3 participants abstained. This shows that the technical guidance activities had a positive and beneficial impact on participants.